Kinerja UMKM di Era Ekonomi Digital: Kajian Literasi Keuangan, Orientasi Kewirausahaan dan Akses Permodalan Dengan Moderasi Teknologi Digital - Chitra Indah Sari; Rizal; Nil Firdaus (MABIS Jurnal Manajemen Bisnis Syariah, 2025)
This study aims to analyze the effect of financial literacy, entrepreneurial orientation, and access to capital on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era, considering the role of digital technology as a mediating variable. The research method uses a quantitative approach with a survey of 100 active MSME players in Indonesia who have been running their businesses for at least two years and utilize digital technology in one aspect of their operations. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The results show that financial literacy, entrepreneurial orientation, and access to capital have a positive and significant effect on MSME performance. Entrepreneurial orientation contributes the most, followed by financial literacy and access to capital. In addition, digital technology was found to mediate the relationship between these three independent variables and MSME performance, strengthening the internal contribution of businesses to increasing competitiveness. These findings confirm that digitalization is not merely an additional tool, but functions as a strategic catalyst in strengthening MSME performance. This study provides practical implications that the government and stakeholders need to expand support for financial literacy, entrepreneurship coaching, and digital-based access to capital so that MSMEs can survive and develop sustainably amid disruption.